Food Security of Fisher Households in Coastal Areas in Indonesia: a Review - Yuli Solihati; Wiwied Tri Dayanti (Journal of Health Science and Pharmacy, 2025)
Background: Food security among fisher households in coastal areas is a critical issue that intersects with both social and economic dimensions. Fisher households often face challenges in accessing sufficient and nutritious food due to their reliance on limited natural resources, uncertain fish catches, and vulnerable socio-economic conditions. Objective: This literature review aims to explore existing research on the food and nutritional security of fisher households, focusing on the factors that influence food security in coastal communities and identifying potential strategies to improve the welfare of fisher households in Indonesia. Methods: A literature review was conducted by analyzing 20 relevant academic journals addressing food and nutritional security among fisher households in coastal regions of Indonesia. The articles were sourced from Google Scholar and selected based on predefined inclusion and exclusion criteria. Results: The findings indicate that economic, social, and environmental factors play significant roles in determining the food security status of fisher households. Low household income often results in a higher proportion of expenditure on food, thereby increasing the risk of food insecurity. Moreover, limited access to natural resources and inadequate infrastructure contribute to food insecurity, especially in remote coastal areas where communities have fewer opportunities to obtain diverse and nutritious food compared to those residing near economic centers. Conclusion: Food security in fisher households is influenced by a combination of economic conditions, accessibility to markets and resources, and the broader socio-economic context of coastal communities. To improve food security, strategies should include income diversification, improved market access, and community education on healthy and sustainable dietary practices. Keywords: Food Security, Fisher Households, Coastal Communities, Economic Welfare, Food Access, Indonesia.